Rez life : an Indian's journey through reservation life - Treuer, David (Atlantic Monthly Press, 2012)
Novelist David Treuer examines Native American reservation life--past and present--illuminating misunderstood contemporary issues of sovereignty, treaty rights, and natural-resource conservation while also exploring crime and poverty, casinos and wealth, and the preservation of native language and culture.